1993
DOI: 10.1021/bi00082a018
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of interaction of HIV reverse transcriptase with primer/template

Abstract: Intrinsic protein fluorescence of reverse transcriptases from HIV-1 and HIV-2 provides a sensitive signal for monitoring the interaction of the enzymes with primer/template duplex molecules. Kd values for 18/36-mer DNA/DNA duplexes were found to be in the range of a few nanomolar (about 3 times higher for the enzyme from HIV-2 than for that from HIV-1). The quenching of protein fluorescence induced on binding primer/template, together with an increase in extrinsic fluorescence on interaction with primer/templa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 36 publications
4
52
0
Order By: Relevance
“…A Kd value of < I nM was obtained by Beard and Wilson (1993). Divita et al (1993a) obtained a Kd value of 1.8 nM at 25 "C from a titration curve that measured binding from the observed changes in intrinsic protein fluorescence. It is evident that a variety of experimental approaches yield Kd values for primerkernplate binding that are predominantly in the low nanomolar range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Kd value of < I nM was obtained by Beard and Wilson (1993). Divita et al (1993a) obtained a Kd value of 1.8 nM at 25 "C from a titration curve that measured binding from the observed changes in intrinsic protein fluorescence. It is evident that a variety of experimental approaches yield Kd values for primerkernplate binding that are predominantly in the low nanomolar range.…”
Section: Discussionmentioning
confidence: 99%
“…From the dissociation rate constant and Kd values, binding rate constants in the range of 106-107 M-I S -I are obtained (Kati et al, 1992;Beard & Wilson, 1993;Hsieh et al, 1993). Stopped-flow kinetics gives a value of 5 x 10' M" s-l (Divita et al, 1993a). Given the slow rate of dissociation of free RT heterodimers to monomers, an estimated tl,* of 53 min at 37 "C, the primer/template binding step is kinetically isolated.…”
Section: Discussionmentioning
confidence: 99%
“…During these interactions it has been proposed that RT under-goes at least three conformational changes. Divita etal. suggested that HIV-1 RT, in the presence of DNA, changes conformation upon binding to nucleic acids (Divita et al, 1993b). The polymerase is thought to undergo a second conformational change subsequent to dNTP binding immediately prior to the chemical catalysis step.…”
Section: Pathway Of Dna Polymerizationmentioning
confidence: 99%
“…HIV-1 RT tightly binds double-stranded nucleic acids with a K^ of 5-38ΠΜ. Structural and biochemical data as well as fluorescence quenching studies suggested that RT binds to DNA by a two step mechanism (Divita et al, 1993b;Kruhoffer et al, 1993). The structure of HIV-1 RT, in the absence of DNA, shows the p66 thumb subdomain folded over the p66 palm subdomain, and coming into contact with the finger subdomain (Raag et al, 1994).…”
Section: Pathway Of Dna Polymerizationmentioning
confidence: 99%
“…HIV-1 RT exhibits a characteristic intrinsic tryptophan fluorescence with a maximal emission at 338 nm due to the 37 tryptophan residues of the enzyme molecule (Divita et al, 1993). The binding of 10 to RT induced a 25% quenching of intrinsic fluorescence.…”
Section: Fluorescence Experiments and Enzymologymentioning
confidence: 99%